# maths

posted by .

differentiate the following function using the composite rule h(x)=e^x(4-x)/6

• maths -

is that e to the power of x(4-x)/6 ?

If so then,

dy/dx = e^[x(4-x)/6] * (2-x)/3
I hope that's right

## Similar Questions

1. ### math

can some one please help me with the following questions as i don't understand them please (a) write down the derivative of each of the functions f(x)=E7x and g(x)=cos(2x) using the product rule differentiate the function k(x)=E7xcos(2x) …
2. ### maths

use the quotient rule to differentiate the following k(t)=e^3t/4-t^2 (-2<t<2)
3. ### maths for science

use the quotient rule to differentiate the following function f(x)=(1+In(x))/(x)
4. ### Maths

Differentiate using the product rule. How do i get from dy/dx = d(uv)/dx = u dv/dx + v du/dx =(5x-2)^3[-6(3-x)^5]+(3-x)^6[15(5x-2)^2] to: =(5x-2)^2(3-x)^5(-30x+12+45-15x) it's an example taken from my text book. Could you help me?
5. ### calculus

Please can someone help. I need to use the composite rule to differentiate the function f(x)=(x^2-6x+23)^3/2. Any help would be greatly appreciated.
6. ### Maths - Calculus

Can anyone help with this...I need to find the derivative of the functions below. If possible please show working so I can try and understand?
7. ### Maths - Calculus

Can anyone help with this...I need to find the derivative of the functions below. If possible please show working so I can try and understand?
8. ### maths

(a)(i)use the composite rule to differentiate the function f(x)=(x^2-6x+23)^(3/2). (ii)use the composite rule and your answer to part (a)(i) to show that the function g(x)=(x-2)/(x^2-6x+23)^(3/2) has derivative g'(x)=(5+9x-2x^2)/(x^2-6x+23)^(5/2). …
9. ### Calculus

I'm having problems with this one. Can't get the right answer. Differentiate the following using the chain rule. f(x) = squareroot(x^2+1)/(3x+1) I know that I can take the whole thing and put it to the (1/2) and differentiate that …